HOW THE COVID-19 OUTBREAK AFFECT THE EFFICIENCY OF ISLAMIC RURAL BANKS? - Titis Miranti; Nur Avni Aulia; Laila Masruro Pimada (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Islamic Rural Banks (BPRS) have an essential function for developing the Micro, Small, and Medium Enterprises (MSME) sector. For the BPRS to exist and not be liquidated, the BPRS needs to maintain its financial efficiency. This study aims to determine the efficiency of a BPRS in East Java. Then, this is to find out what affects the efficiency. Two Stages-Data Envelopment Analysis (DEA) calculate the efficiency. The first stage of data analysis is carried out by assessing the efficiency of the BPRS. The second stage is the analysis of variables that affect efficiency using logistic regression. This analysis also uses the description of the year of the Covid pandemic as a predictor variable. The results of this study found that the BPRS in East Java was categorized as inefficient (inefficiency). However, from the 20 samples used, there are three efficient BPRS based on the average individual BPRS during the 2012-2020 period. Based on logistic regression analysis, it is known that the factors that affect the efficiency of BPRs include Operational Costs and Operating Income, Earning Assets, and the pandemic era.